2007
DOI: 10.1002/hyp.6788
|View full text |Cite
|
Sign up to set email alerts
|

Modelling enhanced infiltration of snowmelt ions into frozen soil

Abstract: Abstract:A model is proposed in which the cumulative load of an ion infiltrating into frozen unsaturated soil can be estimated as a function of meltwater ion concentration and infiltration rate. Assumptions of the model are that the meltwater solution released to the soil surface is conservative, fully mixed within each time step, and that mass and energy are conserved. Infiltration and meltwater concentration are estimated using relationships developed by Gray and Stein respectively. The model suggests that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…They suggested that NO 3 ‐N in runoff from ROS events may be transported relatively conservatively to the stream due to fast runoff rates and limited interaction with subnivean soil. This conservative transport of chemicals during ROS events has also been reported in situations where the soil is partially or completely frozen, limiting infiltration of meltwater (Jones and Pomeroy, 2001; Lilbaek and Pomeroy, 2007). The importance of ROS events to NO 3 ‐N budgets may be especially pronounced in catchments where physiographic characteristics enhance this limited interaction.…”
Section: Introductionmentioning
confidence: 54%
“…They suggested that NO 3 ‐N in runoff from ROS events may be transported relatively conservatively to the stream due to fast runoff rates and limited interaction with subnivean soil. This conservative transport of chemicals during ROS events has also been reported in situations where the soil is partially or completely frozen, limiting infiltration of meltwater (Jones and Pomeroy, 2001; Lilbaek and Pomeroy, 2007). The importance of ROS events to NO 3 ‐N budgets may be especially pronounced in catchments where physiographic characteristics enhance this limited interaction.…”
Section: Introductionmentioning
confidence: 54%
“…This would limit infiltration (e.g. Lillbaek and Pomeroy, 2007) and help to enhance runoff. Summer precipitation (snow + rain) was extremely large in 2008, and in comparison to the dominant and deeply thawed upper bowl area of LSC (maximum thaw depth = 0·71 m), these thinly thawed ground ice‐rich sites (maximum thaw depth = 0·4 m) would likely shed this water rather than storing it.…”
Section: Resultsmentioning
confidence: 99%
“…Using Zhao and Gray's (1999) parametric relationship for the cumulative mass of water that infiltrates a frozen mineral soil, F [kg m −2 ], and Stein et al's (1986) expression for meltwater ion concentration as a function of time, C i (t) [meq m −3 ], Lilbaek and Pomeroy (2007) showed that the temporal association between infiltration rate, f (t) [kg s −1 m −2 ], and meltwater ion concentration, C i (t), is highly non-linear, even though both decline rapidly with time. The study showed that the cumulative infiltration of snowmelt ions is enhanced by initially higher ion concentration in meltwater and infiltration rate.…”
Section: Introductionmentioning
confidence: 99%
“…The model by Lilbaek and Pomeroy (2007) assumes a limited infiltration regime as defined by Granger et al (1984) in which there are neither substantial macropores nor impeding basal ice layers as well as that the meltwater solute is conservative and fully mixed at all times. The use of Zhao and Gray's equation to estimate infiltration to mineral soils under an organic layer was assumed appropriate when the organic layer rapidly transfers water to the mineral soil surface .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation